Faktor-Faktor yang Memengaruhi Ekspor Biji Kakao Indonesia ke Pasar Amerika Serikat - Yudha, Eka Purna; Larasati, Farah; Fadhilah, Adistia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Cocoa is one of the leading commodities in the plantation sector which has an important role and contributes greatly to Indonesia's export activities. Cocoa has the potential to improve the country's economy through international trade between Indonesia and its destination market, the United States, which is known as a world cocoa beans importer. Part of the cocoa that is processed and used as this research material is cocoa beans. This study aims to identify and analyze the factors that influence the export of Indonesian cocoa beans to the United States. The method used is a multiple linear regression analysis method using SPSS software using variables that are processed. These variables are world cocoa bean prices, Indonesian cocoa bean export prices to the United States market, cocoa bean export prices to competing countries (Ecuador), Indonesia's real GDP, GDP real United States, Population of Indonesia and the United States, and Productivity of cocoa beans.